A delayed curing UV adhesive and preparation method thereof

By furanizing and modifying the acrylate compounds and adding thiol monomers and photoinitiators, the curing time is delayed, the bonding strength and thermal stability are improved, and the problems of UV glue curing speed and excessive viscosity are solved, and the effect of complete curing under light-free conditions is achieved.

CN118667452BActive Publication Date: 2025-04-25SHENZHEN PROSPER DOBOND TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410790885.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-04-25
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

Existing UV glues are limited in application due to their fast curing speed, high viscosity, impermissible water corrosion resistance, and poor high temperature stability.

Method used

By furanizing the acrylate compound and adding thiol monomer and photoinitiator, the curing time is delayed, and the bonding strength and thermal stability are improved. Combining component A and component B ensures complete curing of UV glue under light-free conditions.

Benefits of technology

It achieves that the UV glue has a low viscosity before curing, and can be completely cured under dark conditions after ultraviolet light is triggered, with high bonding strength and good thermal stability, and is suitable for bonding of light-transmitting materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the technical field of adhesives, and specifically relates to a delayed curing UV adhesive and a preparation method thereof. The method comprises: 1) taking an acrylate compound and an organic solvent and adding them to a flask, then taking a carboxylic acid halide and a stabilizer and mixing them evenly, dripping the mixed reagent of the carboxylic acid halide and the stabilizer into the flask at a low temperature, and concentrating the solution after the reaction; 2) adding an inhibitor, a photoinitiator, and a mercapto monomer to the flask of step 1) and mixing them evenly to obtain component A; 3) taking a carboxylic acid anhydride compound and solvent A and adding them to a flask, dripping a mixed solution of a polyolefin compound and solvent B at a low temperature and heating the reaction, drying and washing the product to obtain component B; 4) taking component A and component B and mixing them evenly to obtain a delayed curing UV adhesive. The UV adhesive prepared by the present invention can be used as a positioning agent. Under lightless conditions, the UV adhesive can bond materials, and the materials can still be removed intact and bonded again, and begin to cure after being triggered by ultraviolet light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a delayed curing UV adhesive and a preparation method thereof. Background Art

[0002] UV glue, also known as ultraviolet curing glue or photosensitive glue, is an adhesive that needs to be cured by ultraviolet light. UV glue has the advantages of high environmental protection, low flammability, and fast curing speed. It can be cured within a few seconds to tens of seconds by using UV curing devices of different powers, which can significantly improve production efficiency. After curing, UV glue has high bonding strength and can be immediately tested for performance or processed as a finished product. It is widely used in the fixing, bonding, sealing and infusion of materials that are sensitive to temperature and humidity, such as glass crafts, electronic components, laser heads, optical lenses, chips, etc.

[0003] In the bonding process of some materials, UV glue is used as a positioning agent and fixing agent. In order to protect photosensitive materials from the influence of ultraviolet light, it is necessary to ensure that the UV glue has a certain viscosity and can still be easily separated from the photosensitive material. At the same time, it is also necessary to ensure that the UV glue is completely cured under a short-term exposure to ultraviolet light. Otherwise, the optical performance of the photosensitive material will rapidly decrease due to long-term exposure to ultraviolet light. Therefore, a delayed curing UV glue has appeared on the market. The ultraviolet initiator (or photosensitizer) in the UV curing material produces active free radicals or cations under the action of ultraviolet light, which triggers chemical reactions such as monomer polymerization and cross-linking, allowing the UV glue to cure quickly. However, bisphenol A epoxy resins have high viscosity and alicyclic epoxy resins cure too quickly. It is difficult to achieve the above requirements by simply mixing and compounding the two. In addition, the UV glue should have a certain bonding strength after curing.

[0004] Patent CN109385248A discloses an environmentally friendly high-strength UV adhesive and its preparation method, including the following raw materials by weight: 30-45 parts of epoxy acrylate compounds, 30-45 parts of modified polyurethane acrylate compounds, 5-10 parts of honey, 7-12 parts of viscosity enhancers, 22-28 parts of photoinitiators, 18-26 parts of anti-aging agents, 6-10 parts of polyvinyl alcohol, 4-8 parts of dibutyl phthalate, 2-5 parts of silicon micropowder, 3-5 parts of sodium pyrophosphate, 2-4 parts of fragrances, and 12-18 parts of xanthan gum. Although the material has good adhesion to the surface of silver-plated materials, the glue has good thixotropy, good aging resistance, and is environmentally friendly, the research and development process is simple, the cost is low, the UV adhesive is not easy to fall off, and the service life is long, but the material is difficult to be applied in high temperature and high humidity environments, and the applicability is still insufficient. Summary of the invention

[0005] Based on the above content, in order to solve the problem that UV glue is limited in application due to its too fast curing speed, too high viscosity, not resistant to water erosion, and poor high temperature stability, the present invention proposes a delayed curing UV glue and a preparation method thereof.

[0006] The objects of the present invention are:

[0007] 1. Ensure that the UV glue has low viscosity before curing;

[0008] 2. Ensure that the UV glue can be fully cured under dark conditions after being triggered by ultraviolet light.

[0009] To achieve the above objectives, the present invention adopts the following technical solutions.

[0010] A preparation method of delayed curing UV adhesive,

[0011] The method comprises:

[0012] 1) Add an acrylic acid ester compound and an organic solvent into a flask, then add a carboxylic acid halide and a stabilizer and mix them evenly, slowly dropwise add the mixed reagent of the carboxylic acid halide and the stabilizer into the flask at low temperature, and concentrate the solution after the reaction is completed;

[0013] 2) adding the polymerization inhibitor, the photoinitiator and the mercapto monomer to the flask in step 1) and mixing them evenly to obtain component A;

[0014] 3) taking a carboxylic anhydride compound and solvent A into a flask, dropping a mixed solution of a polyolefin compound and solvent B into the flask at low temperature, heating the mixture to react, and drying and washing the product to obtain component B;

[0015] 4) Component A and component B are mixed evenly to obtain a delayed curing UV adhesive.

[0016] As a preference,

[0017] The acrylic acid ester compound in step 1) is butyl acrylate;

[0018] In step 1), the organic solvent is acetone, and the amount used is 0.5-0.7 mL / mL of acrylate compound.

[0019] As a preference,

[0020] Step 1) the carboxylic acid halide is 2-furoyl chloride;

[0021] The stabilizer is dichloromethane, and its dosage is 1.1-1.5 mL / mL carboxylic acid halide;

[0022] The dosage of the mixed reagent is 0.8-1 mL / mL of acrylate compound;

[0023] The low temperature in step 1) is 0-4°C.

[0024] As a preference,

[0025] Step 1) The reaction is carried out at a constant temperature of 25 to 30° C. for 22 to 26 hours;

[0026] Step 1) The concentration is to evaporate the solvent at 56-60° C., and the evaporation is stopped when the product is concentrated to 50-60% VOL of the original volume.

[0027] As a preference,

[0028] Step 2) the polymerization inhibitor is o-triphenol, and its dosage is 0.03-0.05 g / mL acrylate compound;

[0029] Step 2) the photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and its dosage is 0.05-0.1 g / mL acrylate compound;

[0030] In step 2), the mercapto monomer is pentaerythritol tetrakis(3-mercaptopropionate), and its usage is 0.1-0.2 g / mL of acrylate compound.

[0031] As a preference,

[0032] The operation steps of step 1) and step 2) are all carried out under light-proof conditions.

[0033] As a preference,

[0034] Step 3) the carboxylic anhydride compound is maleic anhydride;

[0035] Step 3) the solvent A is ethanol, and its usage is 6-8 mL / g carboxylic anhydride compound;

[0036] Step 3) the low temperature is 5-10°C;

[0037] Step 3) the polyolefin compound is a polyetheramine, and the amount thereof is 1.5 to 2.5 g / g of the carboxylic anhydride compound;

[0038] Step 3) The solvent B is ethanol, and its usage is 6-8 mL / g polyolefin compound.

[0039] As a preference,

[0040] Step 3) The temperature reaction is carried out at 40-45°C for 1.5-2h.

[0041] As a preference,

[0042] Step 4) The component A and the component B are prepared in a mass ratio of (4-6):1.

[0043] A delayed curing UV adhesive.

[0044] In the technical solution of the present invention, the glue of component A has good fluidity and is in a viscous liquid state before being irradiated with ultraviolet rays. Although acrylate compounds have a certain viscosity, the light curing speed of commercially available acrylate compound UV glue is too fast, resulting in limited application of acrylate compound UV glue and failure to provide an operational space for bonding opaque materials. In order to delay its curing time and improve the bonding strength, thermal stability and other properties of the material after curing, and to ensure that the UV glue meets the requirements of low initial viscosity and high one-time curing degree, the present invention modifies the acrylate compound.

[0045] The present invention first furans butyl acrylate, and the furanized butyl acrylate can cooperate with component B to achieve a certain crack repair effect at high temperature, which is convenient for repairing opaque materials. Since the furanized butyl acrylate is self-polymerized in a free radical chain polymerization mode after being triggered by ultraviolet light, the molecular weight increases rapidly, and the viscosity of the system is too large, which not only makes it difficult to remove the target adhesive material, but also has a low degree of adhesive curing and uneven components. In order to delay the curing of the system and reduce the curing shrinkage rate of the UV adhesive, the present invention adds a mercapto monomer tetrakis (3-mercaptopropionic acid) pentaerythritol ester for modification, and since the tetrakis (3-mercaptopropionic acid) pentaerythritol ester has high polymerization activity, a small amount of phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide can initiate the reaction. In the self-polymerization process, the furanized butyl acrylate and the tetrakis (3-mercaptopropionic acid) pentaerythritol ester copolymerize in a free radical step-by-step polymerization mode, which delays the curing of the system and improves the conversion rate of functional groups (C=C, C=O). The elongation at break of UV glue increases with the increase of the amount of mercapto monomer. Mercapto monomer forms thioether structure in UV glue, increases the flexibility of molecular chain, improves the stress shrinkage of UV glue curing, and the material gradually shows tough fracture. However, it is found through experiments that polyester with thioether structure is not resistant to high temperature, and excessive thioether structure will significantly reduce the high temperature stability of UV glue. The initial bonding strength of UV glue increases with the increase of the amount ratio of mercapto monomer, and the bonding strength decreases after curing. In the early stage of curing, since the initial bonding strength of UV glue depends on the reaction of mercapto monomer and butyl acrylate, the reaction rate is fast, which makes the gel point of UV glue advance, so UV glue will produce a larger initial bonding strength at room temperature. However, in the later stage of curing, the bonding strength of UV glue depends on the reaction of hydroxyl group of mercapto monomer attacking epoxy group. The hydroxyl content in the system increases, and the main chain contains a large number of aromatic ring structures and hydroxyl groups, which leads to a decrease in bonding strength after curing, and the curing and setting time will be relatively prolonged, resulting in limited application.

[0046] At the same time, the above text has explained that the photoinitiator does not need to be added in large quantities. If an excessive amount of photoinitiator is added, the copolymerization reaction speed will be too fast, a large amount of heat will be released, and curing will be promoted. The viscosity will increase rapidly, making it difficult for the molecular chain to migrate, the local crosslinking density will be too large, and the stress will increase. The curing shrinkage of the UV glue will not only cause uneven components, but also increase the shrinkage rate of the surface layer, cracks will appear, and the tensile strength will be significantly reduced. In addition, too little photoinitiator will cause the UV glue to be exposed to light and produce fewer initiation active centers, the system curing reaction rate will be slower, and the components will be uniform after crosslinking, but the degree of curing will be lower. In addition, in order to ensure the appearance of the product, the present invention adds a certain amount of o-triphenol.

[0047] In order to further enhance the bonding strength of the UV glue after light curing, the present invention configures a hard monomer component B containing a rigid structure. In addition to the fact that the addition of furan and maleimide can synergistically produce a high-temperature repair effect, the long polyether chain of the polyetheramine in component B is entangled with butyl acrylate, which improves the solvent resistance of the UV glue. The polyetheramine has low viscosity and good compatibility with butyl acrylate, and the reaction is not too violent. According to the characterization, it can be known that polyetheramine can reduce the exothermic temperature of butyl acrylate during curing. The surface of the UV glue is flat after curing, and it can be used for sealing and perfusion of temperature and humidity sensitive materials. In addition to the irreversible covalent chemical bond crosslinking between molecular chains in the UV glue system, there is also -COO - Ionic bonds, -COOH and hydrogen bonds formed by polyetheramine. In the high-temperature repair experiment, some chemical bonds at the cracks are opened, and the high temperature enhances the movement of the molecular chains. Due to the presence of ionic bonds and hydrogen bonds, the distance between the molecular chains is reduced, and the furan in component A and the maleimide in component B are cross-linked. The thermal stability of the UV glue is significantly improved. The higher the furan functional group content, the stronger the thermal stability of the UV glue, but the temperature change of the thermal weight loss of excess 2-furancarbonyl chloride is not large. At the same time, groups such as -COOH promote the combination of molecular chains, making the cross-linking reaction easier to occur. At high temperatures, the UV glue shows an endothermic peak of the cycloaddition reaction, so the temperature range of high-temperature repair of the UV glue can be determined. UV glue shows high selectivity and tolerance to high temperature and high humidity environments.

[0048] When preparing UV glue, as the mass fraction of butyl acrylate increases, the flexible component plays a role in improving the brittleness of the material and the tensile strength of the UV glue will increase. However, if the amount of component B is too little, the bonding strength of the material will be significantly reduced after curing. If the amount of component B is too much, it will be difficult for the molecular chain to migrate during curing, and covalent bonds are prone to breakage. The temperature required for reconnection is high, which will cause the UV glue to fail. In addition, during the high-temperature repair experiment, due to too many reactive sites and too fast reaction, the components of the cured UV glue are uneven, and it is extremely easy to break.

[0049] In addition, in order to further control the curing shrinkage of the system, the power of the UV lamp needs to be controlled during application to avoid the UV glue curing speed being too fast, resulting in the inability to release stress, thereby increasing the curing shrinkage rate. Before UV irradiation, the UV glue has a certain viscosity and fluidity. After the UV glue is irradiated with a fixed intensity and the polymerization reaction is initiated, the UV glue can be cured under lightless conditions, which is convenient for the bonding of opaque materials. In addition, component A and component B have good compatibility, no phase separation phenomenon, and the UV glue components are uniform after curing. In addition, due to the polymerization of multiple monomers and the entanglement of long chains, the surface of the UV glue after curing is dense and hydrophobic, which can be used for the sealing and infusion of electronic components, optical lenses, chips and other humidity-sensitive materials.

[0050] The beneficial effects of the present invention are as follows:

[0051] (1) The UV adhesive prepared by the present invention can be used as a positioning agent. Under lightless conditions, the UV adhesive can bond materials, and the materials can still be removed intact and bonded again, and begin to cure after being triggered by ultraviolet light;

[0052] (2) The UV adhesive prepared by the present invention can be cured under lightless conditions with a high degree of curing after one ultraviolet light initiation, and is suitable for bonding opaque materials;

[0053] (3) The UV adhesive prepared by the present invention has high bonding strength after curing and also has good thermal stability. DETAILED DESCRIPTION

[0054] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0055] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0056] Example 1

[0057] A method for preparing a delayed curing UV adhesive, the method comprising:

[0058] 1) Under light-proof conditions, add 15 mL of butyl acrylate and 10 mL of acetone to a flask, then take 5 mL of 2-furoyl chloride and 7 mL of dichloromethane and mix them evenly. Slowly drop the mixed reagent of 2-furoyl chloride and dichloromethane into the flask at 0°C, keep the temperature at 25°C for 26 hours, evaporate the solvent at 60°C after the reaction is completed, and stop evaporating when the product is concentrated to 50% of the original volume;

[0059] 2) Under light-shielding conditions, 0.45 g of o-triphenol, 0.75 g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 1.5 g of pentaerythritol tetrakis(3-mercaptopropionic acid) were added to the flask in step 1) and mixed evenly to obtain component A;

[0060] 3) 6 g of maleic anhydride and 40 mL of ethanol were added to a flask, and a mixture of 9 g of polyetheramine and 55 mL of ethanol was added dropwise at 5° C. The mixture was kept at 45° C. for 1.5 h, and the product was dried and washed to obtain component B;

[0061] 4) Component A and component B are prepared in a ratio of 4:1 and mixed evenly to obtain a delayed curing UV adhesive.

[0062] The UV adhesive prepared in this example was characterized and its performance tested, and the characterization and testing methods are as follows.

[0063] 1. Characterization of UV glue curing degree:

[0064] The intensity of the UV point light source is 30mW / cm 2 The UV light exposure time is 100s, and the film is placed in a lightless environment for curing, and the curing time of the UV glue is recorded.

[0065] The photocuring kinetics of UV glue was tested using a Fourier transform infrared spectrometer. The changes in the absorption peak of the UV glue before and after curing in a lightless environment were recorded, and the functional group conversion rate was calculated using the following formula:

[0066]

[0067] Where: C is the conversion rate of functional group (C=C, C=O or -SH), %; A1 is the peak area of ​​C=C or -SH after curing, cm -1 ; A2 is the peak area of ​​C=C or -SH before curing, cm -1 ; A m is the peak area of ​​C=O before curing, cm -1 ; A2 is the peak area of ​​C=C or -SH after curing, cm -1 .

[0068] 2. Characterization of curing shrinkage:

[0069] Based on the characterization test (1), a high-precision electronic densitometer was used to measure the density of the UV adhesive and calculate its curing shrinkage. The formula is as follows:

[0070]

[0071] Where: α is the shrinkage rate of UV glue after curing, %; ρ is the density of UV glue after curing, g / mm 3 ; ρ0 is the density of UV glue before curing, g / mm 3 .

[0072] 3. Thermal stability characterization:

[0073] On the basis of characterization test (1), a 10 mm × 5 mm × 0.2 mm area of ​​cured UV glue was taken for thermal stability characterization. The UV glue was heated at a test temperature of 130°C and a holding time of 2 h. If there was no melting phenomenon and the UV glue surface was not sticky, it was recorded as "√", otherwise it was recorded as "×".

[0074] 4. Tensile performance test:

[0075] On the basis of characterization test (1), a 10 mm × 5 mm × 0.2 mm area of ​​cured UV adhesive was taken for tensile property test. At room temperature, the UV adhesive was stretched using an AllroundLine tensile testing machine at a stretching rate of 10 mm / min. The test was repeated 5 times and the average value was taken.

[0076] 5. High temperature repair effect:

[0077] On the basis of characterization test (1), after curing, the UV glue was cut with a knife. The cut was about 5 mm long, 0.1 mm wide and 1 mm deep. The UV glue was kept at 110°C for 30 min. After cooling, the UV glue at the cut was observed to see if it was cross-linked. If it was cross-linked, it was marked as "√", otherwise it was marked as "×".

[0078] 6. Bond strength test:

[0079] The bonded materials and UV adhesive are fixed on the stage of Labthink peel strength tester, and peeled at 180°, with a tensile rate of 100mm / min. The peel force increases by 0.1N per second and gradually increases until peeling begins (the curve grows slowly and enters a plateau period).

[0080] The results are as follows.

[0081]

[0082] The UV glue prepared by the present invention can be used as a positioning agent. Under lightless conditions, the UV glue has a certain viscosity and can bond materials, and the materials can still be removed intact and bonded again. It starts to cure after being triggered by ultraviolet light, and can be completely cured in a relatively short time at room temperature. According to observation, there is no obvious yellowing and no obvious white lines after the UV glue is cured. This is because the thioether structure of the UV glue increases the flexibility of the molecular chain during the curing process, and under greater stress, the ionic bonds and covalent bonds absorb energy, which improves the UV glue curing stress shrinkage. The UV glue surface has no viscosity. Combined with the results in the table, the UV glue prepared by the present invention can be cured under lightless conditions with a high degree of curing after one ultraviolet light initiation, and is suitable for the bonding of opaque materials. At the same time, it can maintain a low curing shrinkage rate and has a high bonding strength after curing.

[0083] At the same time, in addition to the irreversible covalent chemical bonds between molecular chains, there is also -COO - Ionic bonds, -COOH and hydrogen bonds formed by polyetheramine. In the high temperature repair experiment, some chemical bonds at the cracks are opened, and the high temperature enhances the movement of the molecular chains. Due to the presence of ionic bonds and hydrogen bonds, the distance between the molecular chains is reduced, and the furan in component A and the maleimide in component B are cross-linked. The thermal stability of the UV glue is significantly improved, and groups such as -COOH promote the combination of molecular chains, making the cross-linking reaction easier to occur. It can be seen that the UV glue of the present invention has good thermal stability and a certain high temperature repair effect.

[0084] Example 2

[0085] A method for preparing a delayed curing UV adhesive, the method comprising:

[0086] 1) Under light-proof conditions, add 15 mL of butyl acrylate and 10 mL of acetone to a flask, then take 5 mL of 2-furoyl chloride and 7 mL of dichloromethane and mix them evenly. Slowly drop the mixed reagent of 2-furoyl chloride and dichloromethane into the flask at 0°C, keep the temperature at 25°C for 26 hours, evaporate the solvent at 60°C after the reaction is completed, and stop evaporating when the product is concentrated to 50% of the original volume;

[0087] 2) Under light-shielding conditions, 0.45 g of o-triphenol, 0.75 g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2.4 g of pentaerythritol tetrakis(3-mercaptopropionic acid) were added to the flask in step 1) and mixed evenly to obtain component A;

[0088] 3) 6 g of maleic anhydride and 40 mL of ethanol were added to a flask, and a mixture of 9 g of polyetheramine and 55 mL of ethanol was added dropwise at 5° C. The mixture was kept at 45° C. for 1.5 h, and the product was dried and washed to obtain component B;

[0089] 4) Component A and component B are prepared in a ratio of 4:1 and mixed evenly to obtain a delayed curing UV adhesive.

[0090] The UV adhesive prepared in this example was characterized and tested in the same manner as in Example 1, and the results are as follows.

[0091]

[0092] Since furanized butyl acrylate and pentaerythritol tetrakis(3-mercaptopropionic acid) copolymerize in a free radical step-by-step polymerization process during the self-polymerization process, the curing of the system is delayed, and the conversion rate of the double bond functional groups is increased. The elongation at break of the UV glue increases with the increase in the amount of mercapto monomer used. The mercapto monomer forms a thioether structure in the UV glue, increases the flexibility of the molecular chain, improves the stress shrinkage of the UV glue curing, and the material gradually shows tough fracture. According to the results in the above table, the UV glue in this example has a higher bonding strength, and has better thermal stability and high-temperature repair effect at high temperatures.

[0093] Example 3

[0094] A method for preparing a delayed curing UV adhesive, the method comprising:

[0095] 1) Under light-proof conditions, add 15 mL of butyl acrylate and 10 mL of acetone to a flask, then take 5 mL of 2-furoyl chloride and 7 mL of dichloromethane and mix them evenly. Slowly drop the mixed reagent of 2-furoyl chloride and dichloromethane into the flask at 0°C, keep the temperature at 25°C for 26 hours, evaporate the solvent at 60°C after the reaction is completed, and stop evaporating when the product is concentrated to 50% of the original volume;

[0096] 2) Under light-shielding conditions, 0.45 g of o-triphenol, 0.75 g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 3 g of pentaerythritol tetrakis(3-mercaptopropionic acid) were added to the flask in step 1) and mixed evenly to obtain component A;

[0097] 3) 6 g of maleic anhydride and 40 mL of ethanol were added to a flask, and a mixture of 9 g of polyetheramine and 55 mL of ethanol was added dropwise at 5° C. The mixture was kept at 45° C. for 1.5 h, and the product was dried and washed to obtain component B;

[0098] 4) Component A and component B are prepared in a ratio of 4:1 and mixed evenly to obtain a delayed curing UV adhesive.

[0099] The UV adhesive prepared in this example was characterized and tested in the same manner as in Example 1, and the results are as follows.

[0100]

[0101] According to the results of Examples 1 to 3, the initial bonding strength of the UV glue increases with the increase in the amount ratio of the mercapto monomer, and the bonding strength decreases after curing, and finally the bonding strength increases first and then decreases. In the early stage of curing, since the initial bonding strength of the UV glue depends on the reaction of the mercapto monomer and butyl acrylate, the reaction rate is fast, which makes the gel point of the UV glue advance, so the UV glue will produce a larger initial bonding strength at room temperature. In the later stage of curing, the bonding strength of the UV glue depends on the reaction of the hydroxyl group of the mercapto monomer attacking the epoxy group. The hydroxyl content in the system increases, and the main chain contains a large number of aromatic ring structures and hydroxyl groups, which leads to a decrease in bonding strength after curing, and the curing time will be relatively extended.

[0102] In addition, before ultraviolet irradiation, UV glue has certain viscosity and fluidity, and the adhesive layer is in a viscous liquid state. UV glue is irradiated with a fixed intensity. After initiating polymerization, UV glue can be cured under lightless conditions, which is convenient for the bonding of opaque materials. During the self-polymerization of UV glue, furanized butyl acrylate and tetrakis (3-mercaptopropionic acid) pentaerythritol ester are copolymerized in a free radical progressive polymerization mode, which delays the solidification of the system, and component A and component B have good compatibility, no phase separation phenomenon, and the UV glue components are uniform after solidification. In addition, due to the polymerization of multiple monomers and the entanglement of long chains, the surface of UV glue after solidification is dense and hydrophobic, which can be applied to the sealing and perfusion of humidity-sensitive materials such as electronic components, optical lenses, chips, etc. In summary, the delayed curing UV glue prepared by the present invention has a prospect in the field of adhesive technology.

[0103] Comparative Example 1

[0104] A method for preparing a delayed curing UV adhesive, the method comprising:

[0105] 1) Under light-proof conditions, add 15 mL of butyl acrylate and 10 mL of acetone to a flask, then take 5 mL of 2-furoyl chloride and 7 mL of dichloromethane and mix them evenly. Slowly drop the mixed reagent of 2-furoyl chloride and dichloromethane into the flask at 0°C, keep the temperature at 25°C for 26 hours, evaporate the solvent at 60°C after the reaction is completed, and stop evaporating when the product is concentrated to 50% of the original volume;

[0106] 2) Under light-shielding conditions, 0.45 g of o-triphenol, 0.6 g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2.4 g of pentaerythritol tetrakis(3-mercaptopropionic acid) were added to the flask in step 1) and mixed evenly to obtain component A;

[0107] 3) 6 g of maleic anhydride and 40 mL of ethanol were added to a flask, and a mixture of 9 g of polyetheramine and 55 mL of ethanol was added dropwise at 5° C. The mixture was kept at 45° C. for 1.5 h, and the product was dried and washed to obtain component B;

[0108] 4) Component A and component B are prepared in a ratio of 4:1 and mixed evenly to obtain a delayed curing UV adhesive.

[0109] The UV adhesive prepared in this example was characterized and tested in the same manner as in Example 1, and the results are as follows.

[0110]

[0111] According to the results in the above table, compared with Example 2, the tensile strength and bonding strength of the UV glue prepared in this example are significantly reduced. Due to the high polymerization activity of pentaerythritol tetrakis(3-mercaptopropionic acid), a small amount of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide can initiate the reaction. However, too little photoinitiator will result in fewer initiation active centers generated by the UV glue under light irradiation, a slower curing reaction rate of the system, uniform components after cross-linking, but a low degree of curing, and the surface of the UV glue is still sticky.

[0112] Comparative Example 2

[0113] A method for preparing a delayed curing UV adhesive, the method comprising:

[0114] 1) Under light-proof conditions, add 15 mL of butyl acrylate and 10 mL of acetone to a flask, then take 5 mL of 2-furoyl chloride and 7 mL of dichloromethane and mix them evenly. Slowly drop the mixed reagent of 2-furoyl chloride and dichloromethane into the flask at 0°C, keep the temperature at 25°C for 26 hours, evaporate the solvent at 60°C after the reaction is completed, and stop evaporating when the product is concentrated to 50% of the original volume;

[0115] 2) Under light-shielding conditions, 0.45 g of o-triphenol, 1.6 g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2.4 g of pentaerythritol tetrakis(3-mercaptopropionic acid) were added to the flask in step 1) and mixed evenly to obtain component A;

[0116] 3) 6 g of maleic anhydride and 40 mL of ethanol were added to a flask, and a mixture of 9 g of polyetheramine and 55 mL of ethanol was added dropwise at 5° C. The mixture was kept at 45° C. for 1.5 h, and the product was dried and washed to obtain component B;

[0117] 4) Component A and component B are prepared in a ratio of 4:1 and mixed evenly to obtain a delayed curing UV adhesive.

[0118] The UV adhesive prepared in this example was characterized and tested in the same manner as in Example 1, and the results are as follows.

[0119]

[0120]

[0121] According to the results in the above table, in this case, excessive photoinitiator was added, resulting in a too fast copolymerization reaction speed, releasing a large amount of heat, promoting curing, and rapidly increasing viscosity, making it difficult for molecular chains to migrate. The local cross-linking density was too large, the stress increased, and the curing shrinkage of the UV glue was not only uneven in components, but also due to the increased shrinkage rate of the surface layer, cracks appeared, and the tensile strength was significantly reduced.

[0122] Comparative Example 3

[0123] A method for preparing a delayed curing UV adhesive, the method comprising:

[0124] 1) Under light-proof conditions, add 15 mL of butyl acrylate and 10 mL of acetone to a flask, then take 5 mL of 2-furoyl chloride and 7 mL of dichloromethane and mix them evenly. Slowly drop the mixed reagent of 2-furoyl chloride and dichloromethane into the flask at 0°C, keep the temperature at 25°C for 26 hours, evaporate the solvent at 60°C after the reaction is completed, and stop evaporating when the product is concentrated to 50% of the original volume;

[0125] 2) Under light-shielding conditions, 0.45 g of o-triphenol and 0.75 g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide were added to the flask in step 1) and mixed evenly to obtain component A;

[0126] 3) 6 g of maleic anhydride and 40 mL of ethanol were added to a flask, and a mixture of 9 g of polyetheramine and 55 mL of ethanol was added dropwise at 5° C. The mixture was kept at 45° C. for 1.5 h, and the product was dried and washed to obtain component B;

[0127] 4) Component A and component B are prepared in a ratio of 4:1 and mixed evenly to obtain a delayed curing UV adhesive.

[0128] The UV adhesive prepared in this example was characterized and tested in the same manner as in Example 1, and the results are as follows.

[0129]

[0130] According to the results in the above table, in this example, there is no mercapto monomer modification. After the UV glue is initiated by ultraviolet light, it self-polymerizes in the form of free radical chain polymerization, and the molecular weight increases rapidly. Its curing time is relatively fast, which not only makes it difficult to remove the target adhesive material, resulting in limited applications, but also has a low degree of glue curing and uneven components.

[0131] Comparative Example 4

[0132] A method for preparing a delayed curing UV adhesive, the method comprising:

[0133] 1) Under light-proof conditions, add 15 mL of butyl acrylate and 10 mL of acetone to a flask, then take 5 mL of 2-furoyl chloride and 7 mL of dichloromethane and mix them evenly. Slowly drop the mixed reagent of 2-furoyl chloride and dichloromethane into the flask at 0°C, keep the temperature at 25°C for 26 hours, evaporate the solvent at 60°C after the reaction is completed, and stop evaporating when the product is concentrated to 50% of the original volume;

[0134] 2) Under light-shielding conditions, 0.45 g of o-triphenol, 0.75 g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2.4 g of pentaerythritol tetrakis(3-mercaptopropionic acid) were added to the flask in step 1) and mixed evenly to obtain component A;

[0135] 3) 6 g of maleic anhydride and 40 mL of ethanol were added to a flask, and a mixture of 6 g of polyetheramine and 55 mL of ethanol was added dropwise at 5° C. The mixture was kept at 45° C. for 1.5 h, and the product was dried and washed to obtain component B;

[0136] 4) Component A and component B are prepared in a ratio of 4:1 and mixed evenly to obtain a delayed curing UV adhesive.

[0137] The UV adhesive prepared in this example was characterized and tested in the same manner as in Example 1, and the results are as follows.

[0138]

[0139] According to the results in the table, the amount of polyetheramine used in component B is relatively small. Compared with Example 2, since butyl acrylate releases more heat during curing, the curing speed is accelerated, resulting in a decrease in the bonding strength of the UV glue after light curing.

[0140] Comparative Example 5

[0141] A method for preparing a delayed curing UV adhesive, the method comprising:

[0142] 1) Under light-proof conditions, add 15 mL of butyl acrylate and 10 mL of acetone to a flask, then take 5 mL of 2-furoyl chloride and 7 mL of dichloromethane and mix them evenly. Slowly drop the mixed reagent of 2-furoyl chloride and dichloromethane into the flask at 0°C, keep the temperature at 25°C for 26 hours, evaporate the solvent at 60°C after the reaction is completed, and stop evaporating when the product is concentrated to 50% of the original volume;

[0143] 2) Under light-shielding conditions, 0.45 g of o-triphenol, 0.75 g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2.4 g of pentaerythritol tetrakis(3-mercaptopropionic acid) were added to the flask in step 1) and mixed evenly to obtain component A;

[0144] 3) 6 g of maleic anhydride and 40 mL of ethanol were added to a flask, and a mixture of 9 g of polyetheramine and 55 mL of ethanol was added dropwise at 5° C. The mixture was kept at 45° C. for 1.5 h, and the product was dried and washed to obtain component B;

[0145] 4) Component A and component B are prepared in a ratio of 3:1 and mixed evenly to obtain a delayed curing UV adhesive.

[0146] The UV adhesive prepared in this example was characterized and tested in the same manner as in Example 1, and the results are as follows.

[0147]

[0148] When preparing UV glue, this example uses an excessive amount of component B. During curing, the molecular chain is difficult to migrate, and the covalent bond is easily broken. The temperature required for reconnection is high, which will cause the UV glue to fail. In addition, during the high-temperature repair experiment, due to too many reactive sites and too fast reaction, the components of the cured UV glue are uneven, which is extremely easy to break.

[0149] In addition, if the amount of component B is too small, the bonding strength of the material after curing will be significantly reduced. In summary, it is necessary to control the amount of component A and component B to avoid performance degradation.

[0150] Comparative Example 6

[0151] Commercially available acrylic compound UV glue.

[0152] The UV adhesive prepared in this example was characterized and tested in the same manner as in Example 1, and the results are as follows.

[0153]

[0154] The UV glue in this example has a fast light curing speed. Although the surface of the glue layer is dry after curing, the degree of one-time curing is not as good as the UV glue prepared by the present invention. In addition, the acrylic compound UV glue has no high-temperature repair effect, and it is difficult to repair opaque materials. The UV glue in this example has poor tolerance to high temperature and high humidity environments.

Claims

1. A method for preparing a delayed curing UV adhesive, characterized in that: The method comprises: 1) Add an acrylic acid ester compound and an organic solvent into a flask, then add a carboxylic acid halide and a stabilizer and mix them evenly. Slowly drop the mixed reagent of the carboxylic acid halide and the stabilizer into the flask at low temperature, and concentrate the solution after the reaction is completed; 2) Add the polymerization inhibitor, photoinitiator and mercapto monomer to the flask in step 1) and mix them evenly to obtain component A; 3) Take a carboxylic anhydride compound and solvent A into a flask, add a mixed solution of a polyolefin compound and solvent B dropwise at low temperature and heat to react, dry and wash the product to obtain component B; 4) Mix component A and component B evenly to obtain delayed curing UV adhesive; Step 2) the polymerization inhibitor is o-triphenol, and the dosage is 0.03-0.05 g / mL acrylate compound; Step 2) the photoinitiator is phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, and the amount used is 0.05-0.1 g / mL acrylate compound; Step 2) the mercapto monomer is pentaerythritol tetrakis(3-mercaptopropionic acid) ester, and its usage is 0.1-0.2 g / mL acrylate compound; Step 1) and step 2) are performed under light-proof conditions; Step 3) the carboxylic anhydride compound is maleic anhydride; Step 3) the solvent A is ethanol, and the amount thereof is 6-8 mL / g of the carboxylic anhydride compound; Step 3) the low temperature is 5-10°C; Step 3) the polyolefin compound is a polyetheramine, and the amount thereof is 1.5-2.5 g / g of the carboxylic anhydride compound; Step 3) the solvent B is ethanol, and the amount thereof is 6-8 mL / g polyolefin compound; Step 4) The component A and the component B are prepared in a mass ratio of (4-6):

1.

2. The method for preparing a delayed curing UV adhesive according to claim 1, characterized in that: Step 1) the acrylic acid ester compound is butyl acrylate; Step 1) The organic solvent is acetone, and the amount used is 0.5-0.7 mL / mL of acrylate compound.

3. The method for preparing a delayed curing UV adhesive according to claim 1, characterized in that: Step 1) the carboxylic acid halide is 2-furoyl chloride; The stabilizer is dichloromethane, and the amount used is 1.1 to 1.5 mL / mL of carboxylic acid halide; The dosage of the mixed reagent is 0.8-1 mL / mL of acrylate compound; The low temperature in step 1) is 0-4°C.

4. A method for preparing a delayed curing UV adhesive according to claim 1, 2 or 3, characterized in that: Step 1) The reaction is carried out at a constant temperature of 25 to 30 °C for 22 to 26 hours; Step 1) The concentration is to evaporate the solvent at 56-60°C, and the evaporation is stopped when the product is concentrated to 50-60% VOL of the original volume.

5. The method for preparing a delayed curing UV adhesive according to claim 1, characterized in that: Step 3) The temperature-raising reaction is carried out at 40-45°C for 1.5-2 hours.

6. A delayed curing UV adhesive prepared by the method of any one of claims 1 to 5.

Citation Information

Patent Citations

  • Environment-friendly high-strength UV adhesive

    CN109385248A

  • Waterproof high-strength plywood

    CN109233092A

  • Degradable photoresist and application thereof in 3D printing

    CN114773526A